Carbon stock and paper provision in landscapes with forest and Eucalyptus plantations: data estimates, trade-offs and possible scenarios - Rodríguez, Catalina Zuluaga (2020)
Tropical landscapes have experienced many and rapid changes that simultaneously affect several ecosystem services. The absence of strong policies about land-use and land-cover may result in undesirable consequences. Tropical forest landscapes provide several ecosystem services and carbon stock is considered among the essential for global climate regulation. The replacement of natural forests produce changes in the carbon stock and potentially increase the atmospheric CO2 concentrations. Conversely, silviculture areas are important for meeting societal demands, but silvicultural production may result in negative environmental impacts at different scales. Hence, environmental planners should focus on finding strategies that maximize the ES while minimizing trade-offs in heterogeneous landscapes. In order to reach this target, it is urgent to obtain accurate estimates of carbon sequestration and stock at appropriate spatial scales. Also, it is necessary to understand the real contribution of each land-use and land-cover type to the total carbon stock. Then, the development of scenarios could permit the identification of potential trade-offs and the associated negative impacts on the regulation and provisioning services that will impact different stakeholders. With this in mind, we aimed at identifying how the reduction of natural forest cover and the increase of Eucalyptus plantations affect the carbon stock (regulation ecosystem service) and paper provision (provision ecosystem service). For that, (i) we evaluate the differences between biomass values from the Pantropical Aboveground Biomass Density Map (PABDM) and field-based estimates in Brazilian Atlantic Forest fragments. Then, we explore the possible causes for the results of the comparisons and discuss the consequences for environmental planners (chapter 1). (ii) We analyze how the reduction in natural forest cover and the expansion of silviculture affect the carbon stock at the catchment scale. We studied fourteen catchments with a gradient of natural forest and Eucalyptus from 10% to 100% of forest cover. We estimated the aboveground biomass of the forests in the fieldwork and carried out a literature survey of the carbon stock in Brazilian Eucalyptus plantations of different ages (chapter 2); Finally (iii) we identify the potential trade-offs between carbon stock and paper provision in the catchments within the gradient of natural forest cover. We designed a simple conceptual model of drivers and formulate possible scenarios to evaluate the impacts of the main drivers in the carbon stock and paper provision. Our main overall results are: (i) AGB estimates from PABDM maps range 1.2 to 24 times higher than the field-based estimates, evidencing that great attention is needed when using these sources of information in political decision-making; (ii) there are lower carbon stocks in the natural forest than the in silviculture, probably due to the historical human interference on the forest, plus the unexpected producers\' decision to not cutting the Eucalyptus; (iii) scenarios showed the impermanence of carbon stock in Eucalyptus as the principal responsible for the occurrence of ecosystem services trade-offs. This effect arises at values around 20 Mg ha-1 of carbon stock and paper provision and with occurs in catchments with approximately 30% of natural forest cover